The Effect of Giving a Point System in the Model Make A Match Learning Against Participants Learning Competencies Education in Class VIII Junior High School 21 Padang - Nurdiani Nurdiani; Relsas Yogica; Yosi Laila Rahmi; S. Syamsurizal (Universitas Negeri Padang, 2019)
The research problem at junior high school 21 Padang is the learning model that is less varied, the low learning competencies of students from aspects of knowledge, attitudes, and skills. Efforts that can be made are applying the Make A Match learning model on respiratory system material at junior high school 21 Padang. This type of research is an experimental study with a randomized control group posttest only design study design. The population in this study were all class VIII junior high school 21 Padang which were registered in the 2018/2019 Academic Year totaling eight classes. Sampling was done using simple random sampling technique, which was chosen as the research sample was class VIII.4 as the experimental class and class VIII.5 as the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. The hypothesis in this study was tested using the t-test. Based on the results of the students' competency research, the tcount was 3.55> ttable 1.67, in the attitude competency tcount 2.64> ttable 1.67, and in the competency of skills tcount 2.54> ttable 1.67. The conclusion of the study is that the application of the Make A Match model can improve the competency of knowledge, attitudes, and skills of class VIII students of SMPN 21 Padang.